Market Price Signal Prediction Based On Deep Learning Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, many people are venturing into market trading and investment, thus producing many new traders and investors worldwide. The main goal is to gain profit and prevent loss. Most of them are researching global investment opportunities to learn about the market, especially to predict market prices in the future. However, it will become challenging as the financial indicators are very complicated, and it will require a lot of experience and knowledge. The price movement in the price chart also is hard to be predicted when using a fractal indicator. Recently, machine learning and deep learning are the methods for stock market prediction used widely and show the high accuracy of prediction. This paper proposed a deep learning algorithm, Convolutional Neural Network (CNN), to predict the market price signal prediction for daily timeframe charts. This paper aims to develop a market price signal predictor system using the proposed model of deep learning. This paper provided a few literature reviews that related to this research. The evaluation of the signal prediction accuracy using the proposed model is recorded.